RPL39 Was Associated With Sex Differences in Pulmonary Arterial Hypertension - Haixia Wang; Ling Li; Guangyuan Zhou; Lu Wang; Zeang Wu (Canadian Respiratory Journal)
Pulmonary arterial hypertension (PAH) is a malignant cardiovascular disease with a complex etiology, in which several types of cells play important roles. Sex differences in disease susceptibility and survival have been observed in PAH patients, but few studies have analyzed the effect of changes in cell type and number on sex differences in PAH at the single-cell level. In this study, we performed a series of analyses on GSE169471 and GSE228644 datasets and found significant changes in the ratio of several types of cells in male PAH lung tissues. Surprisingly, we found that the ratio of macrophages in male PAH samples was 7 times higher than that in females. Consistently, the ratio of M1 macrophages was also significantly increased in male PAH samples. The different expression genes (DEGs) in macrophages were mainly involved in the ribosome pathway, which is closely related to cell proliferation. Inhibition of ribosomal protein L39 (RPL39), a core gene in the ribosome pathway, can inhibit macrophage proliferation and attenuate the sex differences in PAH. In conclusion, our study suggests that ribosome pathway–associated cell proliferation of macrophages might be associated with sex differences in PAH.